IMPLEMENTASI SISTEM PELATIHAN E-LEARNING TERHADAP KEPUASAN PEGAWAI KEMENTERIAN KELAUTAN DAN PERIKANAN MELALUI APLIKASI E-MILEA - Wahyu Yulianto (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2020)
The current pandemic has disrupted the implementation of training at the Ministry of Marine Affairs and Fisheries (KKP). The training, which is usually done face-to-face, turns into online training (e-learning). The Apparatus Education and Training Center, which originally this year had the target to train Marine and Fisheries apparatuses online, as many as 1080 people changed to 2700 KKP ASN. A budget allocation of approximately 60% was distracted for handling covid-19 so that more training was carried out online using the e-Milea application. E-Milea (electronic millennial learning) is an e-learning training platform developed by the BDA KKP in providing education and training for the development of KKP ASN competencies. Based on these problems, this study aims to analyze the implementation of the e-learning training system on e-Milea user satisfaction. The system quality, information quality, and service quality variables are independent variables and the dependent variable in this study is user satisfaction. The hypothesis tested using Structural Equation Modeling with a total sample of 97 e-Milea users of Entrepreneurship Training Class 2 and 3. The results showed that the system quality, information quality, and service quality had a significant positive effect on user satisfaction. If the CTF can improve the e-learning training system, user satisfaction will also increase. This requires controlling the quality of the system, information, and services so that user satisfaction will be maintained.